Asparaginase-Induced Acute Necrotizing Pancreatitis Resulting in Chronic Pancreatitis and Pseudocyst in an Adult with Acute Lymphocytic Leukemia - Adiwinata, Randy; Waleleng, Bradley Jimmy; Haroen, Harlinda; Rotty, Linda; Gosal, Fandy; Rotty, Luciana; Hendratta, Cecillia; Lasut, Pearla; Winarta, Jeanne; Waleleng, Andrew; Tendean, Michael (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2023)
L-Asparaginase is one of the main chemotherapy regiments for acute lymphocytic leukemia (ALL) management. Acute pancreatitis is one of the serious side effects of l-asparaginase administration and may lead to interruption of chemotherapy cycle. Long term complications may be devastating for patients which include of pseudocyst pancreas and chronic pancreatitis. Asparaginase induced pancreatitis is rare among adult due to the nature of ALL which commonly occurred in children population. The pathophysiology of asparaginase induced pancreatitis is still unclear. Here we present 18-year-old male with ALL and asparaginase induced acute necrotizing pancreatitis which complicated to chronic pancreatitis and pseudocyst.